2014
DOI: 10.1208/s12249-014-0123-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Ca+ 2 Ion Cross-Linked Carboxymethyl Xanthan Gum Tablet Prepared by Wet Granulation Technique

Abstract: Abstract. The objective of this work was to study the release behavior of prednisolone from calcium-crosslinked carboxymethyl xanthan gum (CMXG) tablets in dissolution medium having different pH values prevailing in the gastrointestinal lumen. Xanthan gum (XG) was derivatized to CMXG which was then cross-linked in situ with Ca +2 ion during wet massing step of tablet preparation. Fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry studies did not show any drug-polymer interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…On the other hand, cross-linked SAL alone was found unsuitable as a compression-coating material as the drug was completely released within 45 min with a very short T lag and T rap . When CMXG is brought in contact with water, the interaction between many hydrophilic groups of CMXG and water leads to the formation of a viscous polymer solution around the tablet surface (21,39). Cross-linking of CMXG with Ca +2 ion further restricts the mobility of the polymer chain resulting in the formation of a true gel layer around the tablet surface (34) and reduces the macromolecular mess size (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, cross-linked SAL alone was found unsuitable as a compression-coating material as the drug was completely released within 45 min with a very short T lag and T rap . When CMXG is brought in contact with water, the interaction between many hydrophilic groups of CMXG and water leads to the formation of a viscous polymer solution around the tablet surface (21,39). Cross-linking of CMXG with Ca +2 ion further restricts the mobility of the polymer chain resulting in the formation of a true gel layer around the tablet surface (34) and reduces the macromolecular mess size (19).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we evaluated Ca +2 ion cross-linked CMXG (Ca-CMXG) matrix tablets for colon delivery of prednisolone (PDL) (21). That study revealed that although Ca-CMXG matrix tablets released considerably less amount of drug in the initial 5 h, none of the tablets was able to produce rapid and complete release in the following 5 h, and thus, Ca-CMXG matrix tablets were found unsuitable as colontargeting device.…”
Section: Introductionmentioning
confidence: 99%
“…However, no endothermic melting peak of PRED was evident in the DSC thermograms of the embedded blends. This result suggested the solid‐state transformation of PRED after entrapment within the polymer, indicating an amorphous or solid‐solution state of the drug in the polymer 58,59 . Although PRED is less soluble in water, the presence of hydroxyl groups within its structure facilitated its dispersion into the matrix by forming hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro drug release study was performed as per the method described previously [23]. Six compression-coated tablets were placed in 700 mL 0.1 (M) HCl solution (37 ± 0.5°C) of pH 1.2 contained in 6 vessels of USP-II dissolution rate test apparatus (TDP-06P, Electro Lab, Mumbai, India) and rotated with paddles at 100 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Sustained release of drugs from native xanthan gum tablets is well documented [21, 22]. We previously reported that matrix tablets composed of Ca +2 ion cross-linked carboxymethyl xanthan gum retarded the initial release of prednisolone for a considerable period of time, although complete drug release even in 10 h was not achievable [23]. Subsequently, we developed a compression-coated tablet in which core tablet of prednisolone containing microcrystalline cellulose (MCC, 55 mg), crospovidone (CP, 9 mg), trisodium citrate (TSC, 10 mg), and prednisolone (PDL, 15 mg) was coated with 225 mg of a blend of carboxymethyl xanthan gum (CMXG) and sodium alginate (SAL) in a ratio of 1.5 : 3.5, and the resulting tablet provided T lag , the time required to release 10% or less drug, of 6.06 h followed by a pulse release within 4.36 h, and, thus, the optimized tablet appeared suitable for colon specific delivery of PDL without the intervention of colonic bacterial enzymes in dissolution fluid [24].…”
Section: Introductionmentioning
confidence: 99%